Heterocyclic Chemistry – Old Science or the Forefront of Chemistry? - Reiser, Oliver (Synlett, 2017)
Oliver Reiser studied chemistry at the Universities of Hamburg, Jerusalem and Los Angeles (UCLA) and earned his Ph.D. degree from the University of Hamburg (Prof. Armin de Meijere) in 1989. After postdoctoral stays at IBM Research Center (Dr. Robert D. Miller) and Harvard University (Prof. David A. Evans), he started his independent research in 1992 at the University of Göttingen. In 1996, he moved to the University of Stuttgart as an Associate Professor and in 1997, to the University of Regensburg as Professor of Chemistry. His research group specializes in catalysis starting from renewable resources such as furans and pyrroles toward fine chemicals, natural products and drugs. He is currently serving as President of the International Society of Heterocyclic Chemistry.